The nutrient composition of human milk between 7–10 months postpartum and its contribution to infant energy intake : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Nutrition and Dietetics, Massey University, Albany, New Zealand - Weinberg, Ariella (Massey University, 2025)
Background: Human milk (HM) is the optimal source of nutrition for infants, with exclusive breastfeeding recommended by the World Health Organization and New Zealand Ministry of Health for the first 6 months. Complementary foods are introduced thereafter, while breastfeeding continues into late infancy. HM composition beyond 6 months postpartum remains under researched in New Zealand, with many studies classifying HM from two weeks postpartum as “mature milk,” potentially overlooking changes later in lactation. Understanding how energy is derived from infant milk sources and complementary foods is crucial for accurate assessment of nutrient intakes and evidence-based infant feeding guidelines. Aim: To determine the nutrient composition of human milk between 7–10 months postpartum and its contribution to infant energy intake. Methods: The cross-sectional study included 625 parent-infant dyads from the multi-centred First Food New Zealand (FFNZ) study (Dunedin and Auckland, 2020–2022). This secondary analysis focuses on a subgroup of 121 mothers, with infants aged 7–10 months, who provided HM samples. Demographic and anthropometric measures, 24-hour dietary recalls, and HM intake volume data (via the dose-to-mother stable isotope technique) were collected. Macronutrients (fat, lactose, protein), vitamins (vitamin A, C, E, folate), minerals (Na, Mg, P, K, Ca), and trace elements (Fe, Cu, Se, Zn, I) were analysed using validated methods. Results: Thirteen of 18 nutrients were within reported literature ranges. HM iodine (62.82 µg/L), iron (133.9 µg/L), selenium (10.21 µg/L), and vitamin C (2.39 mg/100 mL) concentrations were lower than reported literature values, whereas vitamin E (0.27 mg/100 mL) and magnesium (34.30 mg/L) were higher. No clear differences were observed across maternal or infant characteristics. Significant differences (p<0.05) in energy intake were observed across feeding groups. Breastfed and formula-fed infants differed in energy from infant milk sources (mean ± SD: 2068 ± 561 kJ/day vs 2251 ± 601 kJ/day) and total energy intake (3239 ± 525 kJ/day vs 3534 ± 609 kJ/day). Additionally, breastfed and mixed-fed infants differed in energy from complementary foods (1170 ± 741 kJ/day vs 1448 ± 728 kJ/day) and total energy intake (3239 ± 525 kJ/day vs 3538 ± 559 kJ/day). All significant differences remained after adjusting for infant age and sex. Conclusion: HM nutrient concentrations at 7–10 months postpartum were broadly consistent with international literature, though lower iodine, iron, and selenium concentrations may place infants at risk of inadequate intake. Differences in energy intakes between feeding groups were also observed. Future work should integrate HM composition with measured HM intakes to clarify HM’s nutrient contribution in late infancy and to refine infant feeding guidelines.
Keywords: 321001 Clinical nutrition